Masculinities in Transition - Robinson, V. author. aut Link
IX, 221 p.
Keywords: Contributing to feminist approaches to masculinities, this book examines men's contextual experiences of masculine identity. Drawing on new data which compares men as they move across and between public and domestic spaces, it explores the implications of this for the nature of contemporary masculinity.